GoFood Merchants’ Digital Platform Interaction, Risk Perception, and Adaptive Strategies in Bali - Purnama, Madek Jeani; Pramartha, Cokorda Rai Adi; Antara, Made Ermawan Yoga (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 14 No 1 (2025): JELIKU Volume 14 No 1, August 2025 - Preliminary Edition (Expected Completion: August 31, 2025), 2025)
The rapid growth of digital food delivery platforms has increased business opportunities for micro, small, and medium-sized enterprises (MSMEs) in Indonesia, particularly through GoFood. However, this dependency exposes merchants to operational risks, especially when service disruptions occur due to driver protests. This study explores the perceptions, risk awareness, and adaptive strategies of GoFood partner merchants in Bali in response to the off-bid demonstration by ojol (online motorcycle taxi) drivers in Jakarta in May 2025. Using a qualitative phenomenological approach, data were collected through in-depth interviews with nineteen food merchants. The findings reveal that merchants with high platform dependence are more vulnerable to service disruptions, prompting them to adopt temporary strategies such as using private couriers, promoting self-pickup, and partnering with regular drivers. However, these strategies are insufficient for long-term risk mitigation. Merchants also expressed concerns about the lack of proactive crisis response from platform providers and called for greater government involvement in mediating conflicts. This study highlights the need for a crisis management framework involving merchants, platforms, and drivers to ensure the resilience of the digital food delivery ecosystem.